A case of early onset adenocarcinoma associated with colorectal polyposis with an unknown germline mutation - Masahiro Zenitani; Hidehito Inagaki; Hiroki Kurahashi; Takaharu Oue (Surgical Case Reports, 2022)
Abstract Background Typically, in cases of adenomatous polyposis, colorectal cancer develops in the third or fourth decade of life. We report the case of a female patient with colorectal polyposis who developed adenocarcinoma at 8 years of age. Case presentation An 8-year-old girl was admitted with a 4-year history of occasional bloody stools. Colonoscopy revealed colon polyposis and histopathological assessment confirmed a well-differentiated adenocarcinoma in the adenomatous polyps, so laparoscopy-assisted proctocolectomy was performed in the lithotomy position by a simultaneous abdominal and anal approach. To completely resect the rectal mucosa, excision was commenced just distal to the dentate line. After the mucosal resection up to the peritoneal reflection level, an inverted muscular cuff was cut circumferentially, and the terminal ileum was pulled through the muscular cuff and anastomosed to the anal canal. Histopathology revealed multiple adenomatous polyps and scattered well-differentiated tubular adenocarcinomas (tub1) in the adenomatous polyps and the non-polypoid mucosal lesions. Because complete resection was achieved, additional adjuvant chemotherapy was not administered. Polymerase chain reaction (PCR)-direct sequencing of the entire coding region and the exon–intron junctions, and real-time PCR of DNA extracted from blood cells, revealed no mutations of either APC or MUTYH. No deletions, duplications, translocations or inversions of APC, MUTYH and GREM1 genes were found using multiplex ligation-dependent probe amplification (MLPA) and G-banding analysis. Multi-gene panels sequencing for polyposis syndromes or hereditary colorectal cancers, and trio-whole exome sequencing was conducted. However, no candidate pathogenic variants of genes were detected in de novo dominant or autosomal recessive model. Somatic mutation of APC was not detected in 4 polyps by loss of heterozygosity analysis at a single nucleotide polymorphism in intron 14. The patient has remained disease-free for 5 years. Currently, the patient is on loperamide and passes stool 5 times/day without any soiling. Conclusions The genetic analysis suggests that she may have a germline mutation at unscreened region of these genes or in unidentified FAP gene. The patient will be carefully followed up for residual rectal carcinoma and for the development of other cancers.